Efficient quantum signature protocol of classical messages - WANG Jian; ZHANG Quan; TANG Chao-jing (Tongxin xuebao)
An efficient quantum signature protocol of classical messages which was based on quantum one-time pad and quantum key distribution was presented.The classical messages of any length could be encoded into the quantum infor-mation of determinate length because hash function was used to generate message digests.Especially for a large number of messages,the length of shared keys and the number of qubits were greatly shortened in the present protocol.Moreover,it was unnecessary for the protocol to use entangled states and only von Neumann measurement was needed.Compared with other quantum signature protocols,the efficiency of the present quantum signature protocol was greatly improved.